Shifts in the clinical epidemiology of severe malaria after scaling up control strategies in Mali - Coulibaly, Drissa; Kone, Abdoulaye K.; Kane, Bourama; Guindo, Bouréima; Tangara, Bourama; Sissoko, Mody; Maiga, Fayçal; Traore, Karim; Diawara, Aichatou; Traore, Amidou; Thera, Ali; Sissoko, Mahamadou S.; et al. (Frontiers in Neurology, 2022)
A decrease in malaria incidence following implementation of control strategies such as use of artemisinin-based combination therapies, insecticide-impregnated nets, intermittent preventive treatment during pregnancy and seasonal malaria chemoprevention (SMC) has been observed in many parts of Africa. We hypothesized that changes in malaria incidence is accompanied by a change in the predominant clinical phenotypes of severe malaria. To test our hypothesis, we used data from a severe malaria case-control study that lasted from 2014–2019 to describe clinical phenotypes of severe forms experienced by participants enrolled in Bandiagara, Bamako, and Sikasso, in Mali. We also analyzed data from hospital records of inpatient children at a national referral hospital in Bamako. Among 97 cases of severe malaria in the case-control study, there was a predominance of severe malarial anemia (49.1%). The frequency of cerebral malaria was 35.4, and 16.5% of cases had a mixed clinical phenotype (concurrent cerebral malaria and severe anemia). National referral hospital record data in 2013–15 showed 24.3% of cases had severe malarial anemia compared to 51.7% with cerebral malaria. In the years after SMC scale-up, severe malarial anemia cases increased to 30.1%, (P = 0.019), whereas cerebral malaria cases decreased to 45.5% (P = 0.025). In addition, the predominant age group for each severe malaria phenotype was the 0–1-year-olds. The decrease in malaria incidence noted with the implementation of control strategies may be associated with a change in the clinical expression patterns of severe malaria, including a potential shift in severe malaria burden to age groups not receiving seasonal malaria chemoprevention.